1997
DOI: 10.2466/pr0.80.1.115-124
|View full text |Cite
|
Sign up to set email alerts
|

Socialization Forces and the Stability of Work Values From Late Adolescence to Early Adulthood

Abstract: The present report is of findings from a longitudinal study of work values. The findings relate to four important areas, (a) the significance of parental socialization in the formation of intrinsic and extrinsic work values, (b) the effect of early employment on intrinsic and extrinsic work values, respectively, (c) the differential effects of these social experiences across ethnic and gender groups, (d) and the stability of intrinsic and extrinsic work values from late adolescence to the early years of adulth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…K. M. Martin and Tuch's (1993) finding confirmed Shapiro's conclusion that "racial disparities in job values continue to exist independent of the influ ences of adult social class membership, family background factors, and job characteristics" (p. 896). Finally, Cotton, Bynum, and Madhere (1997) reported that their findings helped refine previous results reported by Shapiro (1977), and Martin and Tuch (1993), who suggested that, only on the extrinsic dimension did the AfricanAmerican students place greater emphasis on work values than Caucasian students. The pattern for intrinsic work values was simi lar but the difference smaller.…”
Section: Race and Work Valuessupporting
confidence: 73%
“…K. M. Martin and Tuch's (1993) finding confirmed Shapiro's conclusion that "racial disparities in job values continue to exist independent of the influ ences of adult social class membership, family background factors, and job characteristics" (p. 896). Finally, Cotton, Bynum, and Madhere (1997) reported that their findings helped refine previous results reported by Shapiro (1977), and Martin and Tuch (1993), who suggested that, only on the extrinsic dimension did the AfricanAmerican students place greater emphasis on work values than Caucasian students. The pattern for intrinsic work values was simi lar but the difference smaller.…”
Section: Race and Work Valuessupporting
confidence: 73%
“…However, few studies have specifically investigated the extent to which adolescents' views of work and their career aspirations carry over into adulthood (Loughlin & Barling, 2001;Schoon & Parsons, 2002). The studies that have done so have found that socialization forces that affect young people during adolescence continue to influence their work values and career development in adulthood and that these characteristics demonstrate some degree of stability over time, despite changes associated with increased maturity, experience, and education (e.g., Cotton et al, 1997;Jepsen & Choudhuri, 2001;Jepsen & Dickson, 2003;Pryor, 1980;Schoon & Parsons, 2002). Thus, understanding the work-related knowledge of teenagers should contribute to an understanding of the foundation of the process of socialization to work.…”
Section: Sources Of Anticipatory Socialization During Adolescencementioning
confidence: 99%
“…Studies of work values and the work ethic have examined young people's values, attitudes, and orientation toward work (e.g., Cotton, Bynum, & Madhere, 1997;Loughlin & Barling, 2001;Miller, Woehr, & Hudspeth, 2002). Research on work values has distinguished between intrinsic work values, which concern rewards that are inherent in the experience of work (e.g., self-expression, creativity, personal development), and extrinsic work values, which are associated with the job but are external to the work experience (e.g., income, status, security; Ryu & Mortimer, 1996).…”
mentioning
confidence: 99%
“…In the study of work motivation and expectancies researchers have shown that parental aspirations convey to their childrenÕs work expectations and career choices (Hoffman, Hofacker, & Goldsmith, 1992;Marjoribanks, 1987;Martin & Tuch, 1993). In their longitudinal study (1982)(1983)(1984)(1985)(1986) Cotton, Bynum, and Madhere (1997) reported a positive link between the aspirations of parents and their childrenÕs ÔintrinsicÕ and ÔextrinsicÕ motivation to work. Both types of work motivation seem to decline somewhat in the transfer from adolescence to young adulthood.…”
Section: Socialization and The Development Of The Work Ethicmentioning
confidence: 99%